Synthesis, Characterization, and Applications of Silk/Bentonite Clay Composite for Heavy Metal Removal From Aqueous Solution - Wahab, Nasira; Saeed, Muhammad; Ibrahim, Muhammad; Munir, Akhtar; Saleem, Muhammad; Zahra, Manzar; Waseem, Amir (Frontiers in Chemistry, 2019)
Bentonite clay is abundant and low-cost adsorbent and silk fibroin, a naturally occurring protein both have low capacity to remove lethal heavy metal ions from aqueous solution separately. To enhance their metal adsorbing capacity new silk fibroin-based bentonite composite were prepared for improving water quality by eliminating heavy metal ions i.e., lead, cadmium, mercury and chromium. The as-synthesized composite shows better metal sorption capacity than either of them alone. To analyze their structural properties and characteristic functional groups, X-ray diffraction and Fourier-transform infrared spectroscopy were used. The specific surface area for silk/bentonite composite was about 4 m2/g that is smaller than the unmodified bentonite (23 m2/g) which indicates the impregnation of bentonite onto the silk fibroins. Scanning electron microscopy results shows the changes in morphology from plate aggregates to rosette like arrangements. The XRD results of clay/composite shows increase in basal spacing (d001, from 1.55 nm to 3.34 nm) than pristine clay. FTIR results shows the presence of organic moiety in SF clay composite. The mechanism of adsorption was based on complex formation and ion exchange were proposed briefly. Various adsorption isotherms and kinetic models were applied for the removal of Pb(II), Cd(II), Hg(II), and Cr(VI). As the kinetic study was concerned, kinetic data fitted well to pseudo second order kinetics because experimental values of qe are much closer to the calculated values. The adsorption equilibrium was best studied by Langmuir isotherm whose regression coefficient values (0.985-0.995) are best as compare to Freundlich adsorption isotherm (0.954-0.990) and is indicative of homogeneity of adsorption sites on the SF/clay composite. The monolayer adsorption capacity for Cd(II), Pb(II), Hg(II) and Cr(VI) was found to be 11.35, 11.1, 10.5, and 10.2 mg/g respectively.